The Latin American Fund for Irrigated Rice (FLAR) empowered with digital tools to identify CSA options - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Latin American Fund for Irrigated Rice (FLAR) has changed the way of collecting, analyzing, and disseminating information through its members. Perú, Uruguay, Colombia, Brazil, Nicaragua, Chile, and Argentina countries have changed the way of collecting, analyzing, and disseminating information. FLAR has developed the https://riceobservatory.org/ for LAM as the first digital platform of rice for LAM, in this platform tools developed by the D-CSA team are used to make more D-CSA decisions in more than 2.000.000 hectares.